Antifungal prophylaxis in lung transplant: A survey of United States' transplant centers. Issue 7 (23rd June 2019) - Pennington, Kelly M.; Yost, Kathleen J.; Escalante, Patricio; Razonable, Raymund R.; Kennedy, Cassie C.
Abstract: Background: Antifungal prophylaxis strategies for lung transplant recipients vary without consensus or standard of care. Our current study aims to identify antifungal prophylaxis practices in the United States. Methods: From November 29, 2018, to February 15, 2019, we emailed surveys to medical directors of adult lung transplant centers. An alternate physician representative was approached if continued non‐response after three survey attempts. Descriptive statistics were used to report findings. Results: Forty‐four of 62 (71.0%) eligible centers responded. All Organ Procurement and Transplantation Networks were represented. Only four (9.1%) centers used pre‐transplant prophylaxis for prevention of tracheobronchitis (3 of 4) and invasive fungal disease (4 of 4). Thirty‐nine of forty (97.5%) centers used post‐transplant prophylaxis: 36 (90.0%) universal and 3 (7.5%) pre‐emptive/selective prophylaxis. Most centers used nebulized amphotericin with a systemic agent (26 of 36, 72.2%). Thirty‐two of thirty‐six (88.9%) centers continued universal prophylaxis beyond the hospital setting. Duration of prophylaxis ranged from the post‐transplant hospitalization to lifelong with most centers (25 of 36, 69.4%) discontinuing prophylaxis 6 months or less post‐transplant. Conclusion: Most United States' lung transplant centers utilize a universal prophylaxis with nebulized amphotericin and a systemic triazole for 6 months or less post‐transplant. Very few centers use pre‐transplant antifungal prophylaxis.